First report of the female Acanthogryllus asiaticus Gorochov, 1990 (Orthoptera: Gryllidae: Gryllinae) from India and updated description of two crickets of Gryllini - Meena, Ashok Kumar; Swaminathan, Rajamani; Swaminathan, Tatiana (Zootaxa, 2022)
The present paper reports the occurrence of female Acanthogryllus asiaticus Gorochov, 1990 from India and updates the description of Depressogryllus depressiceps (Ebner, 1935); besides, the description of Scapsipedus raychaudhurii Bhowmik, 1967, now classified into the genus Velarifictorus Randell, 1964 [Velarifictorus raychaudhurii (Bhowmik, 1967)] has been revised. Suitable plates with close-up details of the genitalia have been presented in support of the descriptions.